Combined Classical and Flooding Molecular Dynamics Simulations of The Mip-Rapamycin and FKBP12-Rapamycin Complexes - Elisabeth Catherina Widjajakusuma; Monica Frederica; Kornelius Kaweono (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2023)
Macrophage infectivity potentiator (Mip) protein, an essential virulence factor encoded by pathogenic bacteria such as Legionella pneumophila, arises as an interesting new therapeutic target for novel antimicrobials. However, Mip- ligands also interact with FKBP12 protein, a human FKBP exhibiting immunosuppressive effects. Therefore, these ligands are unsuitable antibiotics. Understanding the dynamics and conformations of proteins in the binding pocket is important to predict binding properties and to design new binders for different FKBPs. We performed the 40 ns combined classical and flooding molecular dynamics simulations using additional flooding potential for Mip-rapamycin and FKBP12-rapamycin complexes. Both complexes have different flexibilities and dihedral angle principal component analysis calculated from MD trajectories. As a result, the Mip-rapamycin complex had more conformations than the FKBP12-rapamycin complex. These different features of both complexes at the binding pocket will provide new dues for the design of selective inhibitors of Mip proteins